FORMULATION OF CHILD-FRIENDLY BANTENGAN ARTS POLICY BASED ON MAQASID SYARIAH IN MALANG REGENCY - Titi Rusydiyati Al Kaswy; Mufidah Ch; Musataklima Musataklima (Universitas Nurul Jadid, 2026)
Children’s involvement in the preservation of Bantengan art is part of the implementation of children’s rights to participate, but on the other hand, it can raise concerns that contradict other children’s rights such as the right to education, worship, and rest. Meanwhile, the Child Protection Law emphasizes the obligation to maintain the physical, psychological, and social well-being of children, but the Cultural Advancement Law does not explicitly integrate child protection principles into it. Studies on Bantengan mostly focus on cultural symbolism, community identity, or socio-economic aspects, thus leaving a normative gap regarding how cultural preservation policies can be aligned with the protection of children’s rights. Furthermore, the application of maqasid shari’ah as a normative framework for formulating operational regulations governing children’s participation in preserving Bantengan art is still under-explored in legal studies. This research is a socio-legal field study that uses a statute, conceptual, and disciplinary approach from legal anthropology and sociology of law. Data were collected through interviews, observations, and literature review. Then, it was analyzed using qualitative analysis, resulting in prescriptive legal recommendations. The findings of this study propose a procedural policy framework based on maqasid shari’ah especially the principle of al-daruriyyat al-khams that ensures the preservation of a child-friendly culture, including the protection of children from physical and psychological violence; age limits and children’s roles; the right to education and rest time; parental supervision; educational and inclusive cultural performances; and enhancing the capabilities of Bantengan community. This study contributes theoretically by integrating the sharia of maqasid shari’ah into the formulation of cultural policies and practically by offering a normative framework for local regulations that balance cultural preservation with child protection.